Human rights: a lingua franca for the multiverse - Baldissone, Riccardo (Routledge, 2010)
Within modern Western thought the demand for human freedom and rights was constructed as the statement of the natural endowment of humans with freedom and rights, on the basis of a fundamental human sameness. This immediate sameness entailed an assimilationist bias, which could instead be overcome by focusing on human similarities. Moreover, if human rights are historical products rather than natural prerogatives, human beings are not only bearers, but also producers of rights, and they are entitled both to claim human rights and to participate in their ongoing construction. Human rights as a growing and expanding language could link the multiplicity of human cultures and natures, and thus play the role of a lingua franca for the multiverse.